Implementasi Sistem Pengenalan Wajah Sebagai Automatic Door Lock Menggunakan Modul ESP32 CAM - Difa, M Kelvin; Suroso, Suroso; Endri, Jon (Patria Artha Technological Journal, 2021)
Facial recognition system is a system developed by many technology companies. Face recognition has become a system that is widely used for various purposes such as the development of security systems, identification of identities, as well as processing of an image or film. One of the methods used to create this system is to use the ESP32 CAM module which is connected to the Arduino, where the ESP32 CAM is a module with an OV2640 camera sensor that can be used to take pictures and face recognition. ESP32 CAM is a development of the previous module and has an ESP32 chip with dual connectivity namely WiFi and Bluetooth. The face which is a part of the human body that is often the focus of attention in social interactions because it plays a vital role by showing identity and emotions. Will be used as an indication of the introduction of a person or Face Recognition. The basic principle is that by quoting the face's unique information, the system will read and recognize it. Face recognition is a pattern recognition (pattern recognition). This can be described as a classification of a face whether recognized or not recognized, and once recognized, the face pattern will be stored. The ESP32 CAM that has been connected to the Arduino will detect whether the face is recognized or not, then the data will be sent to the relay and if the face is recognized, the door lock will open automatically, while if the face data is not recognized, the door lock will not open.